2014
DOI: 10.1016/j.ijid.2013.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Association between proinflammatory cytokines and lipid peroxidation in patients with severe dengue disease around defervescence

Abstract: We propose that the oxidative stress response induced by the dengue virus may trigger the inflammatory cytokine responses in dengue severity and thereby contributes to the pathogenesis of the disease; however the interplay between the oxidative response and inflammatory activity in disease virulence needs further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
64
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(72 citation statements)
references
References 37 publications
6
64
0
2
Order By: Relevance
“…The ROS generated during the innate immune response will induce the redox homeostasis mechanism through the activation of antioxidant defence [17]. We have earlier reported that increased levels of inflammatory cytokines along with lipid peroxides in various clinical spectrum of dengue disease [21]. The present study shows that Nox-2 as well as Nrf-2gene expression was attenuated in all study groups including OFI during DOA.…”
Section: Discussionsupporting
confidence: 57%
“…The ROS generated during the innate immune response will induce the redox homeostasis mechanism through the activation of antioxidant defence [17]. We have earlier reported that increased levels of inflammatory cytokines along with lipid peroxides in various clinical spectrum of dengue disease [21]. The present study shows that Nox-2 as well as Nrf-2gene expression was attenuated in all study groups including OFI during DOA.…”
Section: Discussionsupporting
confidence: 57%
“…Ten studies noted affirmatively that their first blood sampling was performed at the febrile phase, which we defined here as <5 days or <96 h from fever onset (Brasier et al, 2012;Butthep et al, 2012;Green et al, 1999a, b;De La Cruz Hern andez et al, 2014;Malavige et al, 2013a;P erez et al, 2004;Soundravally et al, 2014;Wang et al, 2007). The remaining studies had wider blood sampling windows, ranging from 1 to 10 days from symptom onset (Arias et al, 2014;Bozza et al, 2008;Chen et al, 2005;de-Oliveira-Pinto et al, 2012;Guerrero et al, 2013;Houghton-Triviño et al, 2010;Kurane et al, 1991Kurane et al, , 1993Laur et al, 1998;Levy et al, 2010;Del Moral-Hern andez et al, 2014;Nguyen et al, 2004;Suharti et al, 2003).…”
Section: Study Characteristicsmentioning
confidence: 97%
“…Studies differed in the types of immuno-modulating proteins investigated, and the most frequently profiled cytokines and chemokines were TNFa (12/20, 60 %), IFNg (11/20, 55 %), IL-6 (10/20, 50 %), IL-10 (9/20, 45 %), IL-4 (6/20, 30 %) and IFNa (3/20, 15 %). Despite being the most investigated cytokine, TNFa was significantly elevated in DHF patients in only five studies (Houghton-Triviño et al, 2010;Levy et al, 2010;Nguyen et al, 2004;Soundravally et al, 2014;Wang et al, 2007), and one study found no statistical difference in TNFa levels between DF and DHF patients (Laur et al, 1998). The rest of studies reported no statistical difference or did not detect TNFa.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations